Monstres irreals i personatges reals en la narrativa d’Albert Sánchez Piñol: dels tectons a Napoleó - Samper Prunera, Emili (Studia Romanica Posnaniensia, 2025)
The presence of monsters in Albert Sánchez Piñol’s fiction is its narrative backbone and a resource leading to reflect on the supposedly monstrous condition of the unreal creature, as being opposed to the real human person. This monster can have a specific reference from folklore and can be contrasted with a historical figure. This work aims to examine the treatment and characterisation of the monster in Albert Sánchez Piñol’s most recent fiction – El monstre de Santa Helena (2022) and Pregària a Prosèrpina (2023) – as a component of unreality to be contrasted with the component of reality implied by recreating historical characters such as Napoleon or Cicero. The possible links with folklore features and writer’s previous works will be taken as well into account in our analysis.